2007
DOI: 10.23869/bphjbr.13.1.20075
|View full text |Cite
|
Sign up to set email alerts
|

EMBRIOGENESIS SOMATIK ANGGREK BULAN Phalaenopsis amabilis (L.) Bl: STRUKTUR DAN POLA PERKEMBANGAN

Abstract: Research of the structure and development pattern of somatic embryos from callus of leaf explants moon orchid Phalaenopsis amabilis (L) Bl had been done. One year old of plantlets were used as explants sources. Basal leaf of these explants were cultured in Somatic Embryo Induction Medium (SEIM) e.i.: NP(New Phalaenopsis) medium added with 2 mg/L NAA, 1 mg/L BA, 10 g/L sucrose, and 2 g/L gellan gum. Then somatic embryos were transferred to EMM (Embryo Maturation Medium) e.i. NP medium added with 1 mg/L NAA, 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…From histological observation, it appeared that in embryogenic callus (Figure 4a) the tissue composed of living cells (plasm and nucleus looked clear), composed of close meristematic tissue, contained amylum, many small shoots, and candidate of vascular bundles, which was composed of more compact tissue with thicker cell wall Cells in the edge of callus consisted of small cells that had clear nucleus and the cytoplasm was solid. The characteristics of this cell was similar with the characteristics of embryogenic or meristematic cells (Utami et al, 2007).…”
Section: Pelita Perkebunan Volume 31 Number 2 August 2015 Editionsupporting
confidence: 65%
“…From histological observation, it appeared that in embryogenic callus (Figure 4a) the tissue composed of living cells (plasm and nucleus looked clear), composed of close meristematic tissue, contained amylum, many small shoots, and candidate of vascular bundles, which was composed of more compact tissue with thicker cell wall Cells in the edge of callus consisted of small cells that had clear nucleus and the cytoplasm was solid. The characteristics of this cell was similar with the characteristics of embryogenic or meristematic cells (Utami et al, 2007).…”
Section: Pelita Perkebunan Volume 31 Number 2 August 2015 Editionsupporting
confidence: 65%
“…In orchids, Utami et al (2007) found a protein measuring 44 kDa during the induction of somatic embryogenesis of the orchid P. amabilis in vitro culture. The successful formation of the AtRKD4 protein from the Arabidopsis thaliana model plant in the D.lineale orchid transformant plant suggests that the embryonic gene can work well in orchids, even though the gene is derived from dicot plants.…”
Section: Induction and Detection Of Atrkd4 Protein In Orchid Transformant Plants After Being Induced By Using Dex And Tdzmentioning
confidence: 99%
“…It is also a way to support ex situ conservation (Maruyama & Hosoi 2019). Protein detection of AtRKD4 needs to be done because the function of genes is biochemically carried out by proteins which is the result of gene expression and it determines the character of plants at each stage of their development (Utami et al 2007). RKD4 Protein (RWP-RK motif-containing 4 putative transcription factors domain) is one of two sub-family of RWP-RK protein motifs (amino acid sequences consists of arginine (R), tryptophan (W), prolin (P), arginine (R), and lysine (K) proteins located inside the nucleus which are transcription factors based on similarities of form with basic leucine zipper protein and basic helix-loop-helix.…”
Section: Introductionmentioning
confidence: 99%
“…(Gambar 1) dibanding dengan perlakuan A2B3 (Konsentrasi IAA 2 mg/L dan 3 mg/L) pada 7,84 hst. Kalus yang tidak mampu tumbuh sama sekali (Gambar 2) disebabkan oleh kandungan nutrisi pada media yang sudah mulai berkurang (Rianawati, 2009) Utami et al (2007) Kalus anggrek Phalaenopsis amabilis tumbuh pada minggu ke 6 setelah tanam dengan pemberian NAA 0.5 mg/L dan BA 1 mg/L kombinasi antara NAA dan BA ternyata memberikan efek yang terbaik bagi pertumbuhan kalus anggrek P. amabilis. Kalus dapat tumbuh pada bekas luka irisan daun bagian pangkal.…”
Section: Pengaruh Penambahan Iaa Dan Bap Terhadap Waktu Munculnya Kal...unclassified
“…Auksin memiliki kemampuan untuk memperbesar sel lebih baik di bandingkan dengan sitokinin (Indah & Ermavitalini, 2013). Penelitian Utami et al (2007) eksplan daun yang digunakan untuk menghasilkan embrio somatic adalah bagian pangkal daun yang lebih muda secara fisiologis. Pernyataan tersebut di perkuat oleh penelitian Tokuhara & Mii (2001) untuk melakukan kultur yang mengharapkan pertumbuhan kalus, bagian tanaman yang digunakan adalah bagian daun yang masih melakukan perkembangan vegetative termuda.…”
Section: Pengaruh Penambahan Iaa Dan Bap Terhadap Berat Kalus (Mg) Ek...unclassified